Financial distress and access to capital in emerging markets - Guillén, Jorge (2010)
In this paper I study the main determinants of successful reaccess to international capital markets on a set of emerging market countries after a financial crisis. I focus on three components of the reaccess strategy: commitment to pay, ability to pay, and global liquidity. I employ a panel of 49 countries over a nearly 30-year period and apply a simple probit approach to show that, indeed, a sound external position and a sustainable debt profile, accompanied by a favorable global liquidity environment, are the key considerations for creditors considering whether to resume lending.